HALL AND ION SLIP EFFECTS ON THE MHD CONVECTIVE FLOW FOR MIXED CONVECTION BOUNDARY LAYER FLOW OF A NANOFLUID ALONG AN INCLINED PLATE EMBEDDED IN A POROUS MEDIUM - Rao, N. Srinivasa (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the present investigation, the radiative MHD flow of an incom- pressible viscous electrically conducting non-Newtonian nanofluidover an exponentially accelerated vertical porous surface has been considered. Under the influence of slip velocity in a rotating frame, it takes Hall and ion slip impacts into account. Water and ethylene glycol mixture is considered a base Casson fluid. A steady uniform magnetic field is applied under the postulation of a low magnetic Reynolds number. The ramped temperature and time-altering concentration at the surface are considered. First-order consistent chemical reaction and heat absorption are also regarded. Silver and Titania nanoparticles are disseminated in base fluid water and ethylene glycol combination should be formed by a hybrid nanofluid. The Laplace transformation technique is employed on the non-dimensional governing equations to ensure closed-form ana- lytical solutions. The graphical representations scrutinize the effects of physical parameters on the significant flow characteristics. The temperature of Ag-TiO2/WEG nanofluid is relatively superior to that of Casson Ag-WEG nanofluid. Species concentra- tion of Casson hybrid Ag-TiO2/WEG nanofluid decreases with an increase in Schmidt number and chemical reaction parameters. The heat absorption increases the Nusselt number near the surface, while Ag and TiO2 nanoparticle volume fractions tend to lessen it.